2019
DOI: 10.22207/jpam.13.2.56
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Bacterial Pathogens causing Vaginitis in Patients Attending A Tertiary Care Hospital and their Antibiotic Susceptibility Pattern

Abstract: Aerobic vaginitis (AV) is a condition in which the normal vaginal inhabitants are replaced by aerobic bacterial pathogens, triggering a vaginal immune response. AV should be treated promptly. The aim of the present study is to analyse the prevalence of AV in patients with clinical symptoms of vaginitis. High vaginal swabs were collected from 156 women with clinical suspicion of vaginitis , over a period of 1 year. The swabs were subjected to Gram stain and bacterial culture under aerobic conditions. The organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The present study identified the protein synthesis inhibiting antibiotics -Amikacin and Gentamycin as the being most active against gram negative bacteria isolated from the study population based (Table 4). Third generation cephalosporins -Ceftazidime and Cefoperazone/ Sulbactam were most effective against Gram negative isolates with other cell wall inhibitors having activity in less than 29% of cases as documented by Krishnasamy et al (2019). Combination of third generation with β-lactamase inhibitors especially sulbactam increased the efficiency of the drug 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study identified the protein synthesis inhibiting antibiotics -Amikacin and Gentamycin as the being most active against gram negative bacteria isolated from the study population based (Table 4). Third generation cephalosporins -Ceftazidime and Cefoperazone/ Sulbactam were most effective against Gram negative isolates with other cell wall inhibitors having activity in less than 29% of cases as documented by Krishnasamy et al (2019). Combination of third generation with β-lactamase inhibitors especially sulbactam increased the efficiency of the drug 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Women patients in the reproductive age group 19-45 years were included in the study 10 . Patients having genital malignancy, antibiotic utilization by any route in the month prior to sample collection, having TV, Gardnerella vaginalis or Neisseria gonorrhoea and those above or below the reproductive age were excluded from the study 11,12 . A detailed questionnaire on age, medical history, infertility status and relevant parameters was requested and informed consent for inclusion in the study obtained.…”
Section: Methodsmentioning
confidence: 99%